“SHARK”: Mesin sederhana pengolah sampah plastik menjadi bahan bakar alternatif kapal Slerek di Pantai Pengambengan, Bali - Panjaitan, Fenny Crista Anastasia; Samanta, Pinky Natalia (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
The existence of plastic waste on Pengambengan Beach become worrying and needs attention. Jembrana district is the most significant contributor to plastic waste, at around 53.9 tons/day dominated by HDPE and PE (46%) as product packaging waste.. The Jembrana community, dominated by fishermen, experienced an increase in operational cost due to an upsurge in diesel price, which is the primary fuel for Slerek traditional ship in fishing to the sea. Therefore, the high number of plastic waste presented in Jembrana district is potentially utilized to generate alternative diesel fuel using pyrolysis technique. Results showed that the experimental test of “SHARK” machine for 1 hour could produce 800 ml of fuel from 1 kg of chopped plastic waste and spend 600 gram of 3 kg LPG gas. The conversion value of plastic waste into diesel alternative fuel can reduce operational costs by up to 66%. The sustainable application of the “SHARK” machine can help fulfil the fuel needs of local fishermen in fishing and reduce piles of plastic waste in Jembrana district. The calculation showed that the amount of plastic waste produced in Jembrana per day could meet the fuel needs of 107 Slerek ships to the sea.